Teaching and learning in the knowledge society - Fainholc, Beatriz (2008)
The education processes within the knowledge society of the twenty-first century involve a complex analysis and transformation of learning and teaching proposals. The ubiquitous penetration of technology and especially of ICT contributes to new cultural profiles of social, political and economic organizations and of course also has an impact on education. The decentralization, personalization, increased flexibility, technologic convergence, and other effects of telematic networks call for both an extension of educational programs in the framework of lifelong learning programs and also require measures to overcome exclusion in the face of the new social, technologic and economic demands. Strategic learning, the teaching of comprehension, virtual collaborative groups, and teachers as facilitators – both in face to face and remote education – will help to develop autonomy, strengthen communication and technological abilities, and foster problem solving skills in order to make decisions and participate in the improvement of quality of life through flexible structures, open mentalities, and equitable ethical values. Within this framework, learning and teaching in the knowledge society of the twenty-first century will be conceived for personal self regulation and social self sustainable alternative development. The scenarios include creative competencies and flexible attitudes through the practice of comprehensive and critical reading and thinking, emotional education, free expression, contrasted transference into reality, and participation within diversity. The latter implies a respect to local identity to foster the search for universal peace, democratic coexistence and continuous improvement.